2016
DOI: 10.1016/j.jplph.2016.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Acclimation improves salt stress tolerance in Zea mays plants

Abstract: a b s t r a c tPlants exposure to low level salinity activates an array of processes leading to an improvement of plant stress tolerance. Although the beneficial effect of acclimation was demonstrated in many herbaceous species, underlying mechanisms behind this phenomenon remain poorly understood. In the present study we have addressed this issue by investigating ionic mechanisms underlying the process of plant acclimation to salinity stress in Zea mays. Effect of acclimation were examined in two parallel set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
32
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
4
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 52 publications
1
32
0
Order By: Relevance
“…Salinity is one of the major factors limiting the productivity of agricultural crops with severe effects on germination, plant vigour and crop yield [41]. Soybean is categorized as a salt sensitive crop, so during the onset of salt stress within a plant, all the developmental processes are affected [42].…”
Section: Discussionmentioning
confidence: 99%
“…Salinity is one of the major factors limiting the productivity of agricultural crops with severe effects on germination, plant vigour and crop yield [41]. Soybean is categorized as a salt sensitive crop, so during the onset of salt stress within a plant, all the developmental processes are affected [42].…”
Section: Discussionmentioning
confidence: 99%
“…Glycophytic plant species transiently acquire tolerance to lethal levels of high‐salinity stress after short‐term exposure to low, non‐lethal salinity levels, a process known as salt acclimation (Xie et al ). Salt acclimation has been used in many agricultural practices, such as planting maize (Pandolfi et al ), wheat (Janda et al ), and peas (Pandolfi et al ), to enable crops to grow and develop under high‐salinity conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing the expression of ZmSOS1 in the roots and ZmHKT1 in the shoots while decreasing the expression of ZmHKT1 in the roots contributed to decreased Na + concentration in the shoots of the plants treated with DCPTA and could therefore be a key consequence of the effect of DCPTA on plants exposed to salinity stress. In addition, a recent study showed that Na-acclimated maize plants have improved vacuolar Na + sequestration ability in their leaves and can accumulate relatively large amounts of Na + in those organs without any detrimental effects on photosynthetic capacity [47]. It has been proposed that NHX functions in Na + compartmentalization in the vacuole and efflux of Na + from cells [4], and the upregulation of NHX in transgenic plant species such as Brassica napus [48], poplar [49] and tomato [50] has been shown to increase plant salinity tolerance.…”
Section: Discussionmentioning
confidence: 99%